Socio Economic Factors Affecting The Use Of Solid Waste Produced In Kurunegala and Kundasale - Herath H.M.I.S.K; Wanigasundera W.A.D.P; Hitinayake H.M.G.S.B (Indonesia Strategic Sustainability, 2020)
Municipal Garbage Compost (M.S.W.C.) is popular with organic farming in the world. Nearly 100 authorities in Sri Lanka are involved in the production and the timing is right to identify the factors for using M.S.W.C. The cities of Kurunegala and Kundasale were selected to identify socio-economic factors that influence the use of M.S.W.C. Users (45) and non-users (35) M.S.W.C. selected using a simple random sampling method. Data collection was carried out using questionnaires and key informant interviews. The majority (51%) of M.S.W.C. users are in the 36-50 age category and 60% are in the high-income category. Hence, 47% of M.S.W.C. users are vegetable cultivators. The majority (84%) have higher knowledge about the supply of soil fertility nutrients and knowledge about production and application is at a moderate level. The Spearman correlation and multiple linear regression yields monthly income, agricultural land area, farming experience and knowledge of production methods and applications showed a significant relationship with the number of M.S.W.C. use. Discriminant function analysis yields knowledge about soil fertility, productivity, nutrient availability and attitudes about the benefits of using M.S.W.C. leading to M.S.W.C. users and non-users. Conducting interactive drama, multimedia and promotional videos to promote M.S.W.C.